Beneficial health effects of treatment with flotation-REST on anxiety, muscle tension pain, depression and sleep quality. - Szypłowska, Małgorzata; Kuś, Adrian; Gładysz, Konrad; Neścior, Małgorzata; Szpiech, Kamil (Journal of Education, Health and Sport, 2019)
Restricted environmental stimulation therapy (REST) is a method where all the external stimuli are restricted and it is used to relieve stress, anxiety and depression, as well as improving sleep quality. During a session of flotation-REST a patient is lying face-up in a tank filled with high-buoyancy water, allowing the patient to float comfortably on the surface. The tank reduces the external stimulation and allows to achieve a state of deep relaxation. It has many potential health benefits, including reduction of stress, anxiety and depression. A few studies suggested its positive effects on sleep quality too. The purpose of this paper is to evaluate potential positive health effects of flotation-REST.Flotation-REST treatment decreased the degree of stress, anxiety or depression, whereas the patients’ optimism and sleep quality were significantly increased. The results also indicate that the most severe perceived pain intensity was significantly reduced, however low perceived pain intensity was not influenced by the floating technique. It was concluded that flotation-REST has beneficial effects on decreasing stress, anxiety, depression and pain, therefore the method has potential as a complementary treatment of these. However, more studies are warranted to further evaluate the treatments efficacy.